Gender Differences in Blood Pressure Control Among Hypertensive Patients: A Cross‐Sectional Study at a Tertiary Hospital - Hussein Alhawari; Zain Albdour; Sameeha Alshelleh; Joud Musleh; Tala Qouzah; Tala Qudisat; Diala Al‐Sukhon; Karam Albdour (The Journal of Clinical Hypertension)
ABSTRACT Our study aims to assess gender differences in blood pressure (BP) control among hypertensive patients in Jordan and identify factors influencing these differences. We conducted a cross‐sectional study at Jordan University Hospital (JUH), collecting data from 601 hypertensive patients following up in JUH clinics. Patients were eligible if they were >18 years old, diagnosed with hypertension, taking anti‐hypertensive medication for at least 6 months, and had no chronic kidney disease. BP control was defined as systolic BP <140 mmHg and diastolic BP <90 mmHg. Poor BP control was observed in 59.1% of females and 62.7% of males. Females demonstrated better BP control, even though they had lower incomes, lower education levels, and higher BMIs compared to males. Among females, good medication adherence (p = 0.042) was linked to improved control, while stress and a history of preeclampsia were negatively associated (p = 0.01 and p = 0.030, respectively). Among males, concurrent systemic medication use (p = 0.025) was a positive predictor of BP control, whereas smoking negatively impacted BP control (p = 0.019). Home BP monitoring was common but did not improve control in either gender. In conclusion, females showed better outcomes in BP management, largely due to treatment adherence. A history of preeclampsia and high stress was linked to poorer control in females. Both genders were aware of normal BP levels, but females were more preemptive in maintaining control. To improve hypertension care, we should consider these differences when treating patients.